SINTESIS SENYAWA KALKON SERTA UJI AKTIVITAS SEBAGAI ANTIOKSIDAN - I Wayan Suirta (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2016)
Synthesis chalcone compound by reaction between acetofenone and benzaldehyde using natrium hydroxide as catalyst with distil water or ethanol as solvent has been done. The yield was determined using antioxidant activity test with DPPH and GC-MS. The result of synthesis was pale yellow crystal with melting point of 55-570C. The synthesis in distil water yielded 84,98 %, and the formation of crystal was about 1 hour. The synthesis in ethanol resulted 87,68% yield, with the formation of crystal about 15 minutes. The product showed weak antioxidant activity with reduction percentage averaged at 50%. The GC-MS showed the presence of chalcone compound with sufficiently high purity.